A Facile Synthesis of 3-Substituted-2-styryl-4-quinazolones - DASGUPTA, PURBASHA; TAUNK, ARCHANA (Asian Journal of Chemistry, 2010)
2-Methyl-3,1-benzoxazine-4-one (3), generated by cyclizing of N-acetyl-anthranilic acid with ethyl chloroformate in benzene containing triethyl-amine, reacts with primary amine and subsequently aromatic aldehyde when heated under reflux in glacial acetic acid to give 3-substituted 2-styryl-3,4-dihydro-4-quinazolones (7).